Problemas de aprendizaje en los alumnos con necesidades educativas especiales de la escuela Pedro Vicente Maldonado de la provincia de Cotopaxi del cantón Pujilí en el periodo escolar 2014-2015 - Guamán Espinosa, Nancy Fabiola (2015)
In the Teaching Learning process of children and teenagers with special educational needs, it is necessary that teachers make modifications in the regular curriculum, so the knowledge could be assimilated in concrete and meaningful way in the development of student´s academic and personal life. That is the purpose of this research, to develop a guide with Curricular Adaptations that will support teachers in the process, using new methods, learning techniques according to each student, in the research work the statistical method was used, practicing the descriptive statistics which allowed the data collection, analysis, interpretation and mapping of the information obtained. Through the research work it was found that teachers didn´t make changes in the curriculum. We are completely sure that with the present research we will contribute to the teachers of the “Pedro Vicente Maldonado” High School to improve the teaching- learning process of children and teenagers with special educational needs.